Generating multi-level of details for three-dimensional building model using terrestrial laser scanning data - Akmalia, Rizka (2014)
Terrestrial Laser Scanner (TLS) has been used by various applications to measure three-dimensional (3D) objects. Developments in 3D modelling open the possibility to visualize the environment more fascinating. 3D city model, as a city representation, is an essential tools for many applications. City Geographic Markup Language (CityGML) has defined a standard for 3D building models in 3D city model at five different levels of detail (LOD) for enabling the flexibility in visualization. In this research, the advantages of TLS for generating point cloud of building details and the modelling process of point cloud were explored. Point cloud from TLS was used to generate a building model in multi-LOD. Themethodology in this research generatedLOD3, LOD2, and LOD1 from the same point cloud data. Results from this research were models in LOD3, LOD2, and LOD1 in surface models and also in Extensive Markup Language (XML) files. In the data validation, the Root Means Square Error (RMSE) for the LOD3 was 0.037 meter. Based on the CityGML requirement, minimum accuracy for LOD3 is 0.5 meter. The results show that TLS can be used to generate the multi-LODs.